Simulation of Longitudinal Stability Of Helicopter In Forward Flight (Journal of Engineering, 2013)
The present work describes the development of code for trim and longitudinal stability analysis of a helicopter in forward flight. In general, particular use of these codes can be made for parametric investigation of the effects of the external and internal systems integrated to UH-60 helicopters. A forward flight longitudinal dynamic stability code is also developed in the work to solve the longitudinal part of the whole coupled matrix of equations of motion of a helicopter in forward flight. The coupling is eliminated by linearization. The trim analysis results are used as inputs to the dynamic stability code. The forward flight stability code is applied to UH-60 helicopter.